Analysis Of Acceptance Model Technology Theory On Satisfaction And Loyalty In Online Registration Of Outpatient Patients - Ningsih, Putu Oka Prasetia; Suprapto, Sentot Imam; Widyowati, Agustin (Chakra Brahmanda Lentera Institute, 2024)
Background: The on-site registration system often causes various problems, such as long queues and long waiting times in the queue room, the possibility of data input errors due to being done manually, patient discomfort, and access difficulties for long-distance patients. If these aspects of TAM meet patient expectations, it will create patient satisfaction, ultimately resulting in loyal patients. This research aims to determine the influence of perceived ease of use and perceived usefulness on online registration and its impact on patient satisfaction and loyalty Methods: This study employed an explanatory research design with a quantitative approach. The population consisted of all outpatients at Mataram City Regional Hospital, and the sample included 188 respondents. Data were collected using a closed-ended questionnaire with a Likert scale. For data analysis, the study applied covariance-based Structural Equation Modeling (SEM), specifically Partial Least Squares (PLS), using SmartPLS version 3.0. Results: The research findings revealed that perceived ease of use significantly and positively influences the use of the online registration system (t-stat: 4.603 > 1.96); perceived usefulness significantly and positively affects the use of the online registration system (t-stat: 3.697 > 1.96); user attitude significantly and positively impacts the use of the online registration system (t-stat: 4.952 > 1.96); the use of the online registration system significantly and positively affects patient satisfaction (t-stat: 6.503 > 1.96); the use of the online registration system significantly and positively influences patient loyalty (t-stat: 3.730 > 1.96); and satisfaction significantly and positively impacts patient loyalty (t-stat: 4.840 > 1.96) Conclusion: The online registration system, influenced by perceived ease of use, usefulness, and user attitude, significantly enhances patient satisfaction and loyalty. Mataram City Regional Hospital should continue improving the online registration system and evaluating patient satisfaction to boost loyalty.